Living with brain cancer: From researcher to patient - Stephen Chelko; Daniel Fay (The Beryl Institute, 2022)
As an academic researcher, my work-life revolves around testing the efficaciousness of pharmaceutical drugs on the prevention of cardiac dysfunction, arrhythmias, and sudden cardiac death in animal models of heart disease. I never thought I would go from someone studying a life-threatening disease to a patient living with one in twenty-four hours. Yet, that transformation occurred October 8, 2019. I was just appointed to Assistant Professor at Johns Hopkins University School of Medicine (JHUSOM), yet after sitting for my professional headshot I had a grand mal seizure. I cannot recall this event, but I bit the tip of my tongue off, dislocated my right shoulder, and underwent violent contractions. I was rushed to the Emergency Department, thankfully within the same building (JHUSOM). A few scans later, I was told I had 'a mass' in my brain that needed to be removed immediately. Fearing the worst, I followed the advice of my newly appointed neurosurgeon and scheduled surgery for October 19, 2019. I had no time to process what had and what was about to happen. What followed was two years of post-surgical recovery during a global pandemic, my own personal awe in the power of medicine, resurgence of my seizures and tumors, and now - my road to recovery through chemotherapy and radiation. These two years have taught me so much about the day-to-day difficulties patients with chronic diseases live with, strategies I use to cope with my new normal, and most importantly, the necessity of caregivers. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.